2015
DOI: 10.7860/jcdr/2015/14840.6239
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Use in Injured Drivers – An Emergency Room Study in a Regional Tertiary Care Centre of North West India

Abstract: This study has shown that drivers are consuming not only alcohol but other psychoactive drugs also. Indian traffic regulatory authorities are penalising drunk drivers by doing road side breath alcohol testing with no protocols for drug screening. Appropriate measures should be adopted to screen traffic offenders for psychoactive drugs also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…8,9 Studies have shown that 10%-40% of those injured in traffic accidents were under the influence of alcohol. [10][11][12] In the United States, around 300,000 violent assaults per year take place when the perpetrator is under alcohol intoxication. 13 Studies from Australia and New Zealand have shown that around half of the offenders are intoxicated at the time of committing the crime.…”
Section: Original Articlementioning
confidence: 99%
“…8,9 Studies have shown that 10%-40% of those injured in traffic accidents were under the influence of alcohol. [10][11][12] In the United States, around 300,000 violent assaults per year take place when the perpetrator is under alcohol intoxication. 13 Studies from Australia and New Zealand have shown that around half of the offenders are intoxicated at the time of committing the crime.…”
Section: Original Articlementioning
confidence: 99%
“…26 The annual national records of road accidents in India published by the Ministry of Road Transport & Highways, Government of India, mention injuries due to drug and alcohol use in a single category. 19 There are only a few studies on the topic of driving under intoxication, mostly taken from victims brought to emergency departments [27][28][29] and discussing mostly alcohol. There is only one published systematic review from India on driving under intoxication, which included 23 studies.…”
Section: Let There Be Lightmentioning
confidence: 99%
“…6,7 Substance use is a major risk factor for fatal and non-fatal crash injuries. [8][9][10][11] When viewed as a single heterogeneous group comprising alcohol and drug use, substance use is associated with 45% increased odds of adverse crash outcomes and increased risk of pre-admission Emergency Department fatality. 12,13 Alcohol is associated with a two to seven folds increased odds of crash involvement in a crash, [14][15][16] and a 15-fold increased odds of severe injury.…”
Section: Introductionmentioning
confidence: 99%